Development of Disruptive Factors for Livestock Supply Chain - Abd Majid, Nur Amlya; Sahari@Ashaari, Noraidah; Elias, Nur Fazidah; Mohamed, Hazura (ExcelingTech, 2019)
This study is conducted to identify disruptive factors affecting the performance of Small Medium Enterprise supply chain in the livestock industry. The role of supply chain management in the livestock industry starts from selection of breeders, equipment suppliers to distribution of slaughter meat to retailers, distributors and end users. Through a preliminary study that was conducted, several disruptive factors in the supply chain of livestock farming have been identified such as natural disasters, distribution of supplies, the behaviour of the stockman and financial. These disruptions have caused losses to stockman, the supply of meat was affected and caused subsequent losses to the country. In relation to that, to identify what are the other factors occurred other than the preliminary study factors, (i) a set of questionnaires based on previous studies was established and validation of the disruptive factors were evaluated by the expert and the survey will be conducted with the respondents. The findings reveal that the factors of husbandry process, financial, stockman, quality of livestock product, farm facilities, technology, demand, supply, information communication, sales, transportation, government involvement, disaster and syariah compliance have been identified as the main disruptive factors in the disruption model. This disruption model will be tested using a statistical technique to identify which factors contribute significantly to the disruption of the supply chain in the livestock farming industry.